1992
DOI: 10.1093/hmg/1.6.387
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of both APC alleles in an early stage of colon adenomas in a patient with familial adenomatous polyposis (FAP)

Abstract: To examine whether the dosage effect of germ-line mutations in patients with familial adenomatous polyposis (FAP) is sufficient to cause colorectal adenomas, or an additional somatic mutation of the normal allele is required as well, we have investigated somatic mutations of the APC gene in multiple adenomas developed in one FAP patient. In addition to a 5-bp deletion of one allele present constitutionally in this patient, the normal APC allele had been lost in five of seven DNA samples extracted from small ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 0 publications
2
64
0
Order By: Relevance
“…Tumour-suppressor genes such as BRCAJ , RBI (Cavenee et al, 1983), BRCA2 (Gudmundsson et al, 1995), APC (Ichii et al, 1992) and VHL (Tory et al, 1989) have been studied in many families in which there is a germline mutation to those genes, and loss of the wild-type allele has been seen at high frequency in the tumours of patients carrying the mutation. All these genes therefore fulfil the criteria expected of tumoursuppressor genes, namely obeying Knudson's 'two-hit' hypothesis (Knudson, 1971), whereby one defective allele is inherited and the second is inactivated by loss of part or all of the wild-type chromosome (Ponder, 1988).…”
Section: Loss Of Heterozygosity Studies In Tumours From Patients Withmentioning
confidence: 99%
“…Tumour-suppressor genes such as BRCAJ , RBI (Cavenee et al, 1983), BRCA2 (Gudmundsson et al, 1995), APC (Ichii et al, 1992) and VHL (Tory et al, 1989) have been studied in many families in which there is a germline mutation to those genes, and loss of the wild-type allele has been seen at high frequency in the tumours of patients carrying the mutation. All these genes therefore fulfil the criteria expected of tumoursuppressor genes, namely obeying Knudson's 'two-hit' hypothesis (Knudson, 1971), whereby one defective allele is inherited and the second is inactivated by loss of part or all of the wild-type chromosome (Ponder, 1988).…”
Section: Loss Of Heterozygosity Studies In Tumours From Patients Withmentioning
confidence: 99%
“…The APC gene has been proposed as 'the gatekeeper gene' in the colorectal mucosa, and has recently been suggested to be implicated in cell signal transduction affecting processes like cell growth inhibition (Baeg et al, 1995), apoptosis (Browne et al, 1994) and migration (Wong et al, 1996). Studies in humans with FAP, as well as in mice with analogous mutations, have suggested that the rate-limiting step in the tumour initiation is a somatic mutation of the wild-type APC allele inherited from the unaffected parent (Icii et al, 1992;Luongo et al, 1994). APC mutations have also been found in humans in the earliest neoplastic lesions, the dysplastic aberrant crypt foci (Jen et al, 1994).…”
Section: mentioning
confidence: 99%
“…LOH at a particular locus/gene is considered to indicate the presence of a tumour suppressor at that locus (Ponder, 1988), with the LOH event unmasking the recessive mutation. A number of known tumour suppressor genes such as BRCA1 , RB1 (Cavenee et al, 1983), BRCA2 (Gudmundsson et al, 1995), APC (Ichii et al, 1992) and VHL (Tory et al, 1989) have been studied in families in which there is a germline mutation to those genes, and loss of the wild-type allele has been seen at high frequency in the tumours of patients carrying the mutation. All these genes therefore ful®l the criteria expected of tumour suppressor genes, namely obeying Knudson's`two hit' hypothesis (Knudson, 1971), whereby one defective allele is inherited, and the second is inactivated by loss of part or all of the wild-type chromosome (Ponder, 1988).…”
Section: Introductionmentioning
confidence: 99%